Microplastic contamination in the Eurasian otter (Lutra lutra) as a sentinel of land use impacts in central Italy - Sofia Brunetti; Simone Giovacchini; Anna Loy; Michael Di Gioacchino; Armida Sodo; Massimiliano Scalici; Cristina Coccia (Environmental Research, 2026)

Conservation Planning and Reporting Implications of qPCR-based Multi-species eDNA Detection Under EU Environmental Regulations - Simone Giovacchini; Enrico Mirone; Antonia Bruno; Fausto Ramazzotti; Luca Caprotti; Pamela Monaco; Mirko Di Febbraro; Chiara Manfrin; Pushpinder Singh Jamwal; Francesco Belluardo; Andrea Galimberti; Anna Loy (Environmental Management, 2026)
European Union (EU) legislation supports the conservation of endangered freshwater species through the Habitats Directive (HD, 92/43/EEC) and the Water Framework Directive (WFD, 2000/60/EC), and the eradication of Invasive Alien Species (IAS) through the Regulation 1143/2014. Periodic monitoring and reporting on the species listed in these regulations are mandatory for EU Member States. Quantitative PCR environmental DNA (qPCR eDNA) based approaches offer a new cost-effective and sensitive tool that could contribute to these monitoring obligations and to spatial conservation planning. We analysed the results from a qPCR eDNA simultaneous survey of 11 endangered species, four IAS, one pathogen fungus and one translocated fish at 53 central-Italian freshwater sites to produce three scores that could be used to prioritize areas of intervention based on the cumulative presence of native and alien species and their prevalence and co-occurrence. For each site, we proposed a Prioritizing Protection Score (PPS), a Prioritizing Eradication Score (PES), and a Benthic Invertebrates and Fish Score (BIFS) in accordance with HD, Regulation 1143/2014, and WFD. PPS prioritized 39 sites eligible for Natura 2000 designation to achieve the EU target of 30% protected land, PES identified 22 sites for IAS eradication and management, whereas BIFS highlighted 33 sites where freshwater evaluations can benefit from eDNA surveys. Results from the qPCR eDNA survey also revealed 53 new grid cells of occurrence of IAS and species listed in Annexes II, IV and V of HD that will contribute to the next reporting for both the HD and the IAS Regulation.

Comparing traditional vs. environmental DNA monitoring protocols. The case of the Eurasian otter (Lutra lutra) re-expansion in Central Italy - Simone Giovacchini; Enrico Mirone; Pushpinder Singh Jamwal; Pamela Monaco; Fausto Ramazzotti; Emiliano Pioltelli; Andrea Galimberti; Antonia Bruno; Francesco Belluardo; Antonio Canu; Marco Galaverni; Mirko Di Febbraro; et al. (European Journal of Wildlife Research, 2026)
Once widespread in Italy, in the last century the Eurasian otter ( Lutra lutra ) went to the brink of extinction in this country, only surviving in a few southern river basins. Being included in the Habitats Directive 92/43/EEC, it is mandatory for State Members to monitor its conservation status over time, making cost effective and accurate monitoring protocols a relevant issue. We compared the efficiency of environmental DNA (eDNA) and traditional field survey techniques in detecting the presence of Eurasian otter at the border of the current expansion range of the Eurasian otter in Latium, Central Italy. Water sampling for eDNA detection through species-specific assay and systematic field surveys were run in six river basins. Results from the two approaches were compared at the scale of sampling site, 5 km and 10 km radius upstream. Both techniques agreed in revealing the expansion of Eurasian otter in southern Latium and in confirming otter absence in the northern part of the study area. eDNA allowed to detect otters at two more river catchments compared to field surveys, one of which is located northward in a tributary of the river Tiber, and showed a higher detection rate (0.41), both at sampling site (0.06, p = 0.01), 5 km (0.23) or 10 km radius (0.35) scale. These results suggest that eDNA is a more sensitive method in revealing Eurasian otter presence, providing a useful reference for future standardized monitoring of the species at the country level, especially in expansion areas.

Synthetic debris ingestion by carnivorous mammals in aquatic ecosystems: insights from the Eurasian otter (Lutra lutra) in Europe - Álvaro Luna; David León Muez; Ignacio G. Hermosell; Elena Ávila Falcón; Simone Giovacchini; Enrico Mirone; Miguel Ángel Gómez-Serrano; Ángel Fernández González; Hugh Jasman; Arjen de Groot; Václav Beran; Lukáš Poledník; et al. (Environmental Research, 2025)

A non-invasive genetics insight into population structure and recolonization dynamics of the Eurasian otter (Lutra lutra) at the boundary of its Italian core range - Greta Agostini; Anna Loy; Giulia Gentile; Simone Giovacchini; Cecilia De Sanctis; Enrico Mirone; Lorenzo Papaleo; Antonio Petrella; Nicola D’Alessio; Paolo Colangelo (Mammalian Biology, 2025)
During the past century the Eurasian otter ( Lutra lutra ) suffered a drastic decline throughout the rivers of the Italian peninsula, surviving only in Southern Italy. Recent surveys have revealed irrefutable signs (i.e. faeces’ presence) of otter expansion in Central Italy and, specifically in the last 15 years, along rivers of Abruzzo region. Gradually expanding along the Sangro river, otters have also recolonized the Abruzzo, Lazio and Molise National Park (PNALM). To explore both the dispersal dynamics from Southern Italy to Abruzzo and the potential factors that may limit gene flow with PNALM population, we collected faeces (spraints) and anal jelly samples from rivers in Abruzzo and Molise, as well as tissue samples from Southern Italy. We identified 52 specimens using 11 microsatellite loci. Results revealed a significant genetic differentiation between Southern and Central Italy, suggesting a stepping-stone recolonization process. Genetic structure analysis and gene flow estimation indicated that otters followed different recolonization routes, dispersing across the hinterland and along coastal areas. Population structure in Abruzzo is weak and genetic diversity low, consistent with a recent colonization and a founder effect. The N e estimated could indicate the presence of few breeding adults in the PNALM population, but N c estimated and the 18 unique genotypes in the protected area, suggested the hosting of a higher number of individuals than initially assumed. Although otter group in PNALM is showing a favourable conservation status, its genetic diversity is low, making it vulnerable to demographic and environmental stochastic factors. Accordingly, interventions are recommended to favour movements of otters and increase the likelihood of stabilization and expansion of Central Italy’s population.

Where is the best site for wave energy exploitation? Case study along the coast of northern Latium (ITALY) - Francesco Paladini de Mendoza; Simone Bonamano; Giuseppe Stella; Monica Giovacchini; Dario Capizzi; Fulvio Fraticelli; Sergio Muratore; Calogero Burgio; Sergio Scanu; Maximo A. Peviani; Marco Marcelli (Journal of Coastal Conservation, 2016)